Konsep Fiqh Muamalah tentang Mudharabah dan Perkembangannya dalam Islamic Venture Capital - Nufus, Siti Hayati; Zen, Muhamad (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The need for interaction and collaboration is a fundamental trait in human economic life. In the context of the Islamic financial system, this need is accommodated by a financing mechanism that adheres to the principle of profit sharing and shared risk. One of the most relevant and fundamental forms of partnership contracts is Mudharabah. Along with the evolution of global markets and the complexity of technological innovation, there has been a need to adapt this classic framework into modern financial instruments. This study aims to analyze the application of fiqh muamalah mudharabah and its development in Islamic Venture Capital and legal adjustment with classical fiqh. The method applied in this study is a qualitative method by means of literature study. All information obtained is then processed through scientific stages. This study shows that the mudharabah contract in the development of Islamic Venture Capital is very significant, as evidenced by the existence of the contract used and adhering to sharia principles. Islamic Venture Capital aims to support new venture innovation through involvement in the process of developing and forming companies. The financing method of Sharia Venture capital includes: mudharabah, which is a transaction between two parties who work together to obtain profits.